On the study of Malaysia’s private annuity - Nurin Haniah Asmuni,; Purcal, Sachi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Mortality improvement in many countries nowadays has drawn policymakers’ attention towards providing a financially stable retirement scheme for retirees. In some countries like Chile and Switzerland, annuities are common and a successful product with a good retirement benefit. Private annuities specifically designed for Employees Provident Fund members were also introduced in the Malaysian market in 2000. Despite the high annuitisation rate during that time, this product was suspended by the government a year after. Objections towards the scheme included a belief that insurance companies may profit excessively from the scheme and it provided a lack of protection for contributors’ retirement savings. Annuities have been almost non-existent since then. In a recent Malaysian Government Budget an increase in tax relief for income used to purchase annuities seems to promote the development of annuity markets in Malaysia. Until now, there has been a lack of proper analysis in Malaysia to help buyers understand the value of annuities, especially upon retirement. This study aims to calculate the value for money of Malaysia’s private annuities by computing the Money’s Worth Ratio (MWR) and the Annuity Equivalent Wealth (AEW) of the annuity component of recent products. This analysis will be used to evaluate whether Malaysian private annuities are worth buying.